1991
DOI: 10.1136/gut.32.7.727
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic injection sclerosis: effective treatment for bleeding peptic ulcer.

Abstract: One hundred and nine patients presenting with severe haemorrhage from benign peptic ulcers were randomised to either endoscopic injection sclerotherapy using a combination of 1:100000 adrenaline and 5% ethanolamine or to conservative treatment. Only high risk patients with active bleeding or endoscopic stigmata of recent haemorrhage and accessible ulcers were considered. The two groups were well matched for age, shock, haemoglobin concentration, endoscopic findings, and consumption of non-steroidal anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(14 citation statements)
references
References 17 publications
1
11
0
2
Order By: Relevance
“…To achieve endoscopic hemostasis of an upper gastrointestinal hemorrhage, many procedures are used, including local injections of ethanol, 7-9 polidocanol, [13][14][15] and HSE, 10-12 as well as clipping, 4-6 but each has its own disadvantages. Ethanol is used for fixation and hemostasis of a bleeding vessel because of its potent tissue fixing ability, but the alcohol component may cause the ulcerous lesion to spread after the injection, which can injure the adjacent tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve endoscopic hemostasis of an upper gastrointestinal hemorrhage, many procedures are used, including local injections of ethanol, 7-9 polidocanol, [13][14][15] and HSE, 10-12 as well as clipping, 4-6 but each has its own disadvantages. Ethanol is used for fixation and hemostasis of a bleeding vessel because of its potent tissue fixing ability, but the alcohol component may cause the ulcerous lesion to spread after the injection, which can injure the adjacent tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] To treat upper gastrointestinal hemorrhages, methods such as vascular clipping [4][5][6] and local injections [13][14][15] of ethanol, [7][8][9] hypertonic-saline epinephrine (HSE), [10][11][12] and other sclerosing agents [13][14][15] are commonly practiced; however, all of these methods have their own shortcomings. Clipping is done in a direction tangential to the ulcer location without a direct view of the lesion, thus limiting the efficacy of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the effectiveness of injection therapy [33,34,35,36,37,38,39]. The working principle is based on application of vasoconstrictive agents around the bleeding vessel, which simultaneously causes local tamponade.…”
Section: Injection Therapymentioning
confidence: 99%
“…La récidive hémorragique était définie par la présence d'un des éléments suivants [9] : survenue d'une nouvelle hématémèse ou d'un melaena après une selle normale ; extériorisation d'un melaena associée à des modifications hémodynamiques (fréquence cardiaque supérieure à 100 par minute et pression artérielle systolique inférieure à 100 mmHg) [7,[10][11][12] ; persistance d'un melaena, avec nécessité de transfusions sanguines pour maintenir un hématocrite supérieur à 30 % [7] ; extériorisation d'un melaena associée à une chute de l'hémoglobine de plus de deux points en 24 heures [10][11][12] ; anomalies hémodynamiques isolées (pression artérielle systolique inférieure à 100 mmHg ou chute supérieure à 50 mmHg).…”
Section: Endoscopie Oesogastroduodénaleunclassified